More Than Half a Century Teaching EFL in Colombian secondary schools: Tracing Back Our Footprints to Understand the Present - Jesús Alirio Bastidas (Asociación Colombiana de Profesores de Ingles, 2017)
The main theme of the 50th ASOCOPI Conference held in 2015, was an opportunity to celebrate not only its accomplishments, but also to reflect on the situation of the English as a foreign language teaching and learning process in Colombia. The purpose of this article is to share with the readers the results of a study entitled "The History of Teaching English in Colombian High Schools: 1962-1994." The report is based on a documentary analysis and on testimonies of key informants about such topics as: teaching planning, objectives, syllabi, methods, and materials, and their impact on the history of teaching English as a foreign language. Conclusions will be drawn at the end of the article.